INTERFIRM RELATIONSHIPS: EVOLUTIONARY PERSPECTIVE - Stańczyk-Hugiet, Ewa (Ekonomika, 2013)
Abstract. The aim of the study was to demonstrate that the inter-organizational relationships form the framework of modern business. The common analysis of interfirm relationships is based exclusively on the relational view. The article is focused on the evolutionary and relational approach to management. In this respect, relationships are exemplified in the form of the adaptation mechanism used in the environment while making a selection. The author argues that organizational relationships are an expression of the variation processes that organizations use as the mechanisms of adaptation. Such a perspective is an original approach to the explanation of evolution and of the mechanisms of contemporary competitive advantage. The article is based on the reasoning based on a critical analysis of the existing research in this area, supported by results of the author’s own qualitative research. The main findings of the study outline the possibilities to survive in the current business settings and are related to the relationships; in a wider sense, interfirm relationships are an important mechanism driving evolution. Key words: evolution, interfirm relationships, variation, adaptation